The Use of Wordwall Media Based on Problem Based Learning and Its Impact on Students' Mathematics Learning Outcomes - Devika Rindi Anastasya Putri; Gupo Matvayodha; Minnah EL Widdah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research was motivated by the low mathematics learning outcomes of students and the use of conventional, passive learning media that made students feel bored during the learn-ing process. Monotonous and less engaging learning activities caused students to lose moti-vation to learn. In addition, the lack of opportunities for students to directly experience and practice the learning material became an obstacle in understanding the concepts being taught. Therefore, efforts were needed to improve students’ learning outcomes by providing treatment through more interactive learning media based on problem solving, namely Wordwall media based on Problem Based Learning (PBL). The purpose of this study was to determine whether there was a significant effect of using Wordwall media based on PBL on the mathematics learning outcomes of Grade III students. This study employed a quantita-tive approach using a one-group pretest-posttest design. Data were collected through ques-tionnaires and analyzed using normality tests and t-tests. The results showed an increase in questionnaire scores before and after the use of Wordwall media based on PBL, with the average score increasing from 6.8 to 15.5. The researcher found that the use of Wordwall media based on PBL had a significant effect on the learning outcomes of Grade III students. The significance test result was 0.000, and since 0.000 < 0.05, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. This indicates that the use of Wordwall media based on PBL had a significant effect on students’ learning outcomes.